Your air pollution makes me sick!: Estimating the spatial spillover effects of PM2.5 emissions on emergency room visits in Chile - Mauricio Sarrias; Anita Molina-Varas (REGION, 2022)
This study quantifies the spillover effects of PM2.5 emissions on emergency room visits due to respiratory diseases in Chile. We use several spatial panel methods and models controlling also for the potential endogeneity of air quality. Our estimates show that the spillover effects are downward biased when this endogeneity is ignored. Furthermore, using the estimates from our preferred model, we find that about 65% of the total emergency room visits in Chile are due to PM2.5 emissions generated in the same municipality, whereas the remaining 35% can be attributed to pollutants emitted in a different spatial unit. In economic terms, increasing PM2.5 emissions in one thousand tonnes yields to an increase of 98,010 USD of annual costs for ER health facilities due to spillover effects, whereas the total costs (considering indirect and direct effects) amounts to 283,855 USD.
Keywords: 330; Air pollution; PM2.5 emissions; Spatial spillover effect; Public health; Instrumental variable; Spatial panel models